Effect of facemask use on cognitive function during a maximal running aerobic fitness test - Slimani, M.; Paravlic, A.; Abazovic, E.; Znazen, H.; Bragazzi, N. L. (Frontiers in Physiology, 2022)
Background: The aim of the present randomized, crossover study was to determine the physiological and cognitive function responses while wearing a facemask during a maximal running aerobic fitness test.